Water scarcity and the impact of improved irrigation management: a CGE analysis - Alvaro Calzadilla; Katrin Rehdanz; Richard S. J. Tol (Kiel Institute for the World Economy (IfW), 2008)
We use the new version of the GTAP-W model to analyze the economy-wide impacts of enhanced irrigation efficiency. The new production structure of the model, which introduces a differentiation between rainfed and irrigated crops, allows a better understanding of the use of water resources in agricultural sectors. The results indicate that a water policy directed to improvements in irrigation efficiency in water-stressed regions is not beneficial for all. For water-stressed regions the effects on welfare and demand for water are mostly positive. For non-water scarce regions the results are more mixed and mostly negative. Global water savings are achieved. Not only regions where irrigation efficiency changes are able to save water, but also other regions are pushed to conserve water.
Keywords: D58; Q17; Q25; 330; Computable general equilibrium; irrigation; water policy; water scarcity; irrigation efficiency; Bewässerung; Wassermangel; Wasserpolitik; Wirtschaftliche Effizienz; Bewässerungslandwirtschaft; Allgemeines Gleichgewicht; Theorie; Welt